2000
DOI: 10.1161/01.res.86.12.1245
|View full text |Cite
|
Sign up to set email alerts
|

Human Vascular Adhesion Protein-1 (VAP-1) Plays a Critical Role in Lymphocyte–Endothelial Cell Adhesion Cascade Under Shear

Abstract: Lymphocyte binding to vascular endothelium is a prerequisite for the movement of immune cells from the blood into lymphoid tissues and into sites of inflammation. Human vascular adhesion protein-1 (VAP-1) is an endothelial glycoprotein involved in this interaction. It also displays an enzymatic (monoamine oxidase) activity. Here we examined how recombinant human VAP-1 mediates lymphocyte binding using rotatory and flow chamber binding assays. VAP-1 cDNA transfected into an endothelial cell line, which does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Previous results have indicated that full-length human SSAO transfected into HEC retains its adhesion function for freshly isolated PBMC (Salmi et al, 2000). The efficacy and specificity of enzymatic inhibitors at blocking such interactions in static conditions were evaluated in our study using LJP 1207 and other small molecule inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results have indicated that full-length human SSAO transfected into HEC retains its adhesion function for freshly isolated PBMC (Salmi et al, 2000). The efficacy and specificity of enzymatic inhibitors at blocking such interactions in static conditions were evaluated in our study using LJP 1207 and other small molecule inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in line with the data from frozen section assays, because the contributions of VAP-1 to the binding of these leukocyte subsets to synovial vasculature were also almost equal. In contrast, P-selectin, which accounts for the superior adhesion of mucosal macrophages to synovial venules, is lacking from these transfectants (24). Thus, VAP-1 can indeed support binding of all mononuclear leukocyte classes isolated from IBD gut.…”
Section: Recombinant Vap-1 Can Support Binding Of All Mucosal Leukocymentioning
confidence: 93%
“…In brief, Ax cells are a spontaneously immortalized cell line originating from endothelial cells of rat high endothelial vessels. The parental cells have lost their capacity to bind lymphocytes in vitro, but VAP-1 transfection reconstitutes the adhesion cascade (23,24). The VAP-1 or mock (ϭcontrol) transfectants were plated on microscopic slides within wax-pen circles.…”
Section: Transfectant Binding Assaymentioning
confidence: 99%
“…13,17 CHO cells expressing the extracellular regions of Siglec-11 and Siglec-G fused to the green fluorescent protein and membrane anchored through glycosylphosphatidylinositol were developed using a novel expression system (D.M.O. and P.R.C., manuscript in preparation).…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
“…and P.R.C., manuscript in preparation). The enzymatically inactive mutant CHO-VAP-1Y471F and the RGD mutant CHO-VAP-1D720A have been generated as described by Koskinen et al 7 and Salmi et al, 17 respectively.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%